General practitioners' role in improving health care in care homes: a realist review. (4th July 2022) - Chadborn, Neil H; Devi, Reena; Goodman, Claire; Williams, Christopher D; Sartain, Kate; Gordon, Adam L
Abstract: Background: Despite recent focus on improving health care in care homes, it is unclear what role general practitioners (GPs) should play. To provide evidence for future practice we set out to explore how GPs have been involved in such improvements. Methods: Realist review incorporated theory-driven literature searches and stakeholder interviews, supplemented by focussed searches on GP-led medication reviews and end-of-life care. Medline, Embase, CINAHL, PsycInfo, Web of Science, and the Cochrane library were searched. Grey literature was identified through internet searches and professional networks. Studies were included based upon relevance. Data were coded to develop and test contexts, mechanisms, and outcomes for improvements involving GPs. Results: Evidence was synthesized from 30 articles. Programme theories described: (i) "negotiated working with GPs, " where other professionals led improvement and GPs provided expertise; and (ii) "GP involvement in national/regional improvement programmes." The expertise of GPs was vital to many improvement programmes, with their medical expertise or role as coordinators of primary care proving pivotal. GPs had limited training in quality improvement (QI) and care home improvement work had to be negotiated in the context of wider primary care commitments. Conclusions: GPs are central to QI in health care in care homes. Their contributions relate to their specialist expertise and recognition as leaders of primary care but are challenged by available time and resources to develop this role.